WTWO memoir extracts. Issue 1 (1st April 2022) - Wheale, Nigel
Reading Proust's A la Recherche du Temps Perdu again, always a completely immersive experience for me, I was struck again by the way in which the smallest details of that life become resonant, and make the text so eloquent, utterly involving a reader willing to give themselves up to the work. I was inspired to recall distant details of my own childhood in the West Midlands, and then of a period in a place that appears 'remote' from the mainland United Kingdom. These are two extracts from what will become a longer memoir, though not stretching to Proust's twelve luminous volumes.